Perancangan Sistem Transaksi Non-Tunai Berbasis QR Code di Platform Android - Jay Idoan Sihotang; Rawlson Yoshua Limbong (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2020)
Nowadays the development of technology affects many aspects in life, including financial transaction. In Universitas Advent Indonesia, the payment still using conventional method alias using cash for payments. That causes some possibility of error on payments, and also the users can’t trace their payments history. The application developed is expected to become a payments alternative in campus. The application developed based on old system requirement analysis and developed using Android with PHP as a backend. The payment process is validated using QR Code, both to make transactions between sellers and users, as well as fellow users. The results of the study are a QR Code-based payment application that can run well and is tested both functionally and in appearance.